Wonderful objects-signalizators in karachay-balkarian magical fairytales - Farizat H. Gulieva (Zanukoeva) (Кавказология)
This article explores an area of Karachay-Balkarian fairy-tales, that has been inadequately studied – the classification and characterization of the remarkable objects, featured in magical and magical-heroic fairy-tales of the specified ethnic group. The aim of the research conducted in this case was to analyze signaling devices – objects, used to send a specific signal, message or information. An analysis of the significated set of extraordinary items indicated the potential of further division with the allocation of resources: a) calling an assistant, b) reporting on the condition of the protagonist (owner / donor, their associates and companions), c) messages of peril / alert (i.e., fulfilling the role of modern signaling). The first two groups of annunciator are created to support the main characters, whereas the objects of the third category act as a hindrance to the goal and are owned by their antagonists. It has been discovered, that the considered excellent methods of communication have their origin in the ancient ideas and beliefs of their creator people (animism, totemism, fetishism), and they are founded on sympathetic (contagious / partial / contact) magic. It is observed, that additional detailed examination of wonderful objects and the formation of an appropriate index will not only enrich knowledge of the poetics of the Karachay-Balkarian fairy-tale itself, but will also permit their data to be integrated into the national and worldwide fairy-tale fund and will facilitate comparative studies.